Inisiasi Pembentukan Kube untuk Pengrajin Pandai Besi di Desa Limbang Jaya, Tanjung Batu, Ogan Ilir - Nazeli Adnan; Alghifari Mahdi Igamo; Sri Andaiyani; M Komri Yusuf (Jurnal Pemberdayaan Umat, 2022)
Purposes: This service activity aims to build collective awareness about the potential for social capital and initiate the formation of a Joint Business Group (KUBE) for blacksmith craftsmen in Limbang Jaya village. Research Methodology: The Faculty of Economics, Universitas Sriwijaya has conducted socialization to the blacksmith craftsmen of Limbang Jaya Village 1. This community service activity was carried out on 2 until 9 October 2021. The method of implementing the activity was in the form of providing socialization. The implementation team provides material related to what is meant by KUBE. As an evaluation of the activities, the implementing team provided a questionnaire form to be filled out by the participants. Results: Based on the results of the evaluation conducted, twenty people who were participants in the activity stated that KUBE could be a solution to the problems they faced through partnerships with groups, associations, and government institutions. Limitations: The limitation in this activity is that there is no involvement of parties directly related to the KUBE program. As a result, the material presented in the KUBE socialization activity only uses references from several sources such as journals and government regulations. Contributions: The benefit of this activity is to increase the understanding of the people of Limbang Jaya Village 1 about the importance of managing positive social interactions that have been established into social capital that can be developed to improve family welfare.